Learning to Save: How Financial Management Learning Influences Student Saving Behavior through Financial Literacy? - Sitti Hajerah Hasyim; Nurjannah (Citakonsultindo, 2026)
Global concerns about young people’s financial vulnerability, rising digital consumption, and limited saving discipline have made student financial behavior an important issue in higher education. This study examines the influence of financial management learning on students’ saving behavior through financial literacy among Economics Education students at Universitas Negeri Makassar. Using a quantitative explanatory approach, data were collected from 54 students selected through purposive sampling and analyzed using path analysis with SPSS. The findings show that financial management learning positively affects financial literacy and saving behavior, while financial literacy also positively influences saving behavior. More importantly, financial literacy mediates the relationship between financial management learning and saving behavior, indicating that financial literacy acts as a bridge that transforms financial learning into practical saving habits. These findings suggest that financial management learning should integrate practical financial literacy activities to strengthen students’ responsible saving behavior.